Early development of esophageal squamous cell cancer: Stem cells, cellular origins and early clone evolution. (28th February 2023) - Liao, Guobin; Tang, Jun; Bai, Jianying
Abstract: Esophageal squamous cell carcinoma (ESCC), a highly malignant cancer with poor prognosis, is an example of the classical view of cancer development based on stem cell origin and multistep progression. In the past five years, the applications of large-scale sequencing and single-cell sequencing have expanded to human esophageal normal tissues and precancerous lesions, which, coupled with the application of transgenic lineage tracing technology in mouse models, has provided a more comprehensive and detailed understanding of esophageal stem cell heterogeneity and early clonal evolution of ESCC. In this review, we discuss the heterogeneity of esophageal basal-layer stem cells and their potential relationship with cells of ESCC origin. We present evidence that expansion of NOTCH1 mutants may call into play an evolutionarily conserved anti-cancer mechanism and mold the model of early clonal evolution in ESCCs. Finally, we discuss the potential avenues in this context. This review provides a focused understanding of the early development of ESCC, as a background for early tumor detection, intervention, and prevention strategies. Highlights: This review provides all-rounded evidence for the early development esophageal cancer. Unlike rodent, human esophagus contains slow-cycling stem cell niches, which may be an evolutionary anti-cancer mechanism. Some driver mutants in ESCC may play a tumor-braking role in normal and precancerous stages. NOTCH1 mutants impede carcinogenesis and mold a punctuated early evolutionary model of ESCC. The punctuated evolution model suggests the need to refine our understanding of precancerous lesions.